2022
DOI: 10.1111/iwj.13942
|View full text |Cite
|
Sign up to set email alerts
|

Differences in prophylactic performance across wound dressing types used to protect from device‐related pressure ulcers caused by a continuous positive airway pressure mask

Abstract: Prolonged use of continuous positive airway pressure masks, as often required for non‐invasive ventilation, involves a risk for facial tissue breakdown due to the sustained deformations caused by tightening of the stiff mask surfaces to the head and the moist environment. The risk of developing mask‐related facial injuries can be reduced through suitable cushioning materials placed at the skin‐mask interfaces to spread the localised contact forces and disperse the surface and internal tissue stresses. Using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…For example, excessive dressing strain may develop under compression bandaging or medical devices, or when subjected to the bodyweight as in a non-offloaded diabetes-related foot ulcer (DFU). 5,22,23,[27][28][29] Orlov and Gefen 23,30 recently reported that the compressive stiffness of certain foam dressings compressed to 50% strain can reach approximately 300 kPa, that is, $3.5 times the mean compressive skin stiffness reported by McKee et al, 26 which indicates that currently, the biomechanical compatibility of foam dressings with skin is not always optimal. 23 The chemistry of the raw foam material and the details of the manufacturing process of foaming eventually determine the strength and stiffness of the final foam material.…”
Section: The Stiffness Of Foams and How They Relate To Foam Density A...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, excessive dressing strain may develop under compression bandaging or medical devices, or when subjected to the bodyweight as in a non-offloaded diabetes-related foot ulcer (DFU). 5,22,23,[27][28][29] Orlov and Gefen 23,30 recently reported that the compressive stiffness of certain foam dressings compressed to 50% strain can reach approximately 300 kPa, that is, $3.5 times the mean compressive skin stiffness reported by McKee et al, 26 which indicates that currently, the biomechanical compatibility of foam dressings with skin is not always optimal. 23 The chemistry of the raw foam material and the details of the manufacturing process of foaming eventually determine the strength and stiffness of the final foam material.…”
Section: The Stiffness Of Foams and How They Relate To Foam Density A...mentioning
confidence: 99%
“…5,22,23,[27][28][29] Orlov and Gefen 23,30 recently reported that the compressive stiffness of certain foam dressings compressed to 50% strain can reach approximately 300 kPa, that is, $3.5 times the mean compressive skin stiffness reported by McKee et al, 26 which indicates that currently, the biomechanical compatibility of foam dressings with skin is not always optimal. 23 The chemistry of the raw foam material and the details of the manufacturing process of foaming eventually determine the strength and stiffness of the final foam material. In particular, these factors influence both the properties of the solid polymer phase and the microarchitectural characteristics of the porosity of the foam, that is, the percentage and shape of the microscopic void spaces…”
Section: The Stiffness Of Foams and How They Relate To Foam Density A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has primarily focused on the stiffness and anisotropy of multilayer dressings and their outer coefficient of friction (COF). 10,15,[22][23][24][25][26][27][28][29] This extensive volume of published work supported the development of clinical guidelines for the use of prophylactic dressings, including during the COVID-19 pandemic time, and provided specific design guidance optimizing dressing materials and structures for PUP, which ultimately resulted in evidence-based recommendations for healthcare practitioners and administrators who make purchase decisions to prevent PUs in their facilities. [30][31][32][33] Our current study aims to expand upon the above existing literature, by investigating the internal energy absorption mechanism of multilayer dressings and providing valuable insights into how these dressings mitigate the forces exerted on soft tissues, thereby advancing the understanding of PUP strategies by means of dressings.…”
Section: Introductionmentioning
confidence: 99%
“…The literature published by the AG research group quantified the stress relief in soft tissues at the heels as well as at the sacral region and defined quantitative protective performance and endurance metrics of dressings in prophylactic use, by means of a variety of material measurements and computer modelling and simulation methods. Previous research has primarily focused on the stiffness and anisotropy of multilayer dressings and their outer coefficient of friction (COF) 10,15,22–29 . This extensive volume of published work supported the development of clinical guidelines for the use of prophylactic dressings, including during the COVID‐19 pandemic time, and provided specific design guidance optimizing dressing materials and structures for PUP, which ultimately resulted in evidence‐based recommendations for healthcare practitioners and administrators who make purchase decisions to prevent PUs in their facilities 30–33 …”
Section: Introductionmentioning
confidence: 99%